Sarana dan Prasarana Pendidikan Menurut Al-Qur’an dan Hadist - Saputra, Mohammad Febri Irawan; Abdurrahman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research examines the Al-Qur'an and Hadith guidelines regarding educational facilities and infrastructure and their relevance in the context of modern education. Using document analysis, observation and interview methods, this research found that physical facilities such as classrooms, libraries and modern technology, as well as non-physical infrastructure such as moral and spiritual values, have a significant role in supporting learning. Al-Qur'an verses such as QS. Al-'Alaq verses 1-5 and QS. Al-Mujadilah verse 11, as well as the hadiths of Rasulullah SAW, emphasize the importance of providing adequate educational facilities. The results of the research show that the implementation of Islamic values ​​in the management of educational facilities creates a balance between physical and spiritual aspects, thereby supporting the formation of students' character and improving the quality of learning in a sustainable manner.